Experimental study on the dynamic behavior of steel frames during progressive collapse. (February 2021) - Xie, Fuzhe; Gu, Bin; Qian, Hai
Abstract: To study the dynamic behavior of steel frames after a sudden column failure scenario, an experimental study was performed on a steel frame with three stories by employing an air cylinder to simulate the sudden failure of a column. The experimental results indicate that the remaining structure underwent a large plastic deformation and developed a distinct catenary action in the beams, and this action was more substantial for the first-floor beams compared to the other floor beams. A finite element model (FEM) was established and validated based on the experimental results. The influence of the material strain rate in the structural progressive collapse was analyzed. Comparing the results obtained in the numerical simulation and those obtained using the Department of Defense (DoD) standard equation, indicated that the dynamic increase factor is in the range of 1–2 when conducting static inelastic analysis on steel frames. The equation of the dynamic increase factor in the DoD standard can accurately reflect the dynamic effect of steel frames to a certain extent. However, the results provided by this equation monotonously decrease with the increase in the structural plastic deformation and do not correctly predict the rebound of the dynamic increase factor when the structural material enters the strengthening stage. Graphical abstract: The dynamic behavior of steel frames was investigated based on an experimental study on a steel frame with three stories by adopting an air cylinder to simulate the sudden column failure. A finite element model was validated, and parametrical analyses were conducted on the dynamic increase factor and the influence of material strain rate, which indicates that the equation of the dynamic increase factor in the DoD standard can accurately reflect the dynamic effect of steel frames and the material strain rate cannot be neglected in progressive collapse analysis. Unlabelled Image Highlights: Performing an experimental study on a steel frame by employing an air cylinder to simulate a sudden column failure. Investigation on the dynamic behavior and load transfer path of steel frame during collapse process. Analyzing the development of catenary action and the influence of material strain rate. Study on the dynamic increase factor used in progressive collapse analysis of steel frames.